2014
DOI: 10.1002/cncr.28925
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease detected by coronary computed tomography angiography in adult survivors of childhood Hodgkin lymphoma

Abstract: BACKGROUND Hodgkin lymphoma (HL) survivors have significant cardiovascular risk and require long-term surveillance. This study assessed the prevalence of coronary artery disease (CAD) by coronary computed tomographic angiography (CCTA) in adult survivors of childhood HL. METHODS Thirty-one HL survivors, 13 (42%) treated with radiation therapy (RT) only and 18 (58%) with multimodal therapy, underwent CCTA, echocardiography, electrocardiography (ECG), and treadmill stress testing. Obstructive CAD was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…In fact, using CT angiography screening in a pilot study of Hodgkin lymphoma survivors from the SJLIFE cohort, we found obstructive and non-obstructive coronary disease, with 67% of the lesions located in the proximal coronary circulation. (35)…”
Section: Discussionmentioning
confidence: 99%
“…In fact, using CT angiography screening in a pilot study of Hodgkin lymphoma survivors from the SJLIFE cohort, we found obstructive and non-obstructive coronary disease, with 67% of the lesions located in the proximal coronary circulation. (35)…”
Section: Discussionmentioning
confidence: 99%
“…72 Coronary artery disease, detected with computed tomography angiography, was prevalent among 39% of 31 survivors of HL (median age, 40 years [range, 26-55 years]) exposed to chest radiation during childhood. 73 Finally, Sulicka et al reported a chronic proinflammatory state among 27 survivors of childhood ALL (age range, 18-27 years) when compared with normal controls. 74 Survivors of ALL exhibited elevated levels of pentraxin-3, soluble vascular cell adhesion molecule-1, osteoprotegerin, tumor necrosis factor-related apoptosis-inducing ligand, and counts of intermediate monocytes.…”
Section: Frailty In Childhood Cancer Survivors/ness Et Almentioning
confidence: 99%
“…Survivors of Wilms tumor, leukemia, CNS tumors, germ cell tumors, malignant bone tumors, and HL were found to be at greatest risk . Coronary artery disease, detected with computed tomography angiography, was prevalent among 39% of 31 survivors of HL (median age, 40 years [range, 26‐55 years]) exposed to chest radiation during childhood . Finally, Sulicka et al reported a chronic proinflammatory state among 27 survivors of childhood ALL (age range, 18‐27 years) when compared with normal controls .…”
Section: Introductionmentioning
confidence: 99%
“…In a study of screening echocardiography for more than 1800 adult survivors of childhood cancer treated with anthracycline chemotherapy (+/-radiation to the left chest), asymptomatic CAD was found in 69 patients (3.8%) and newly identified (not previously diagnosed) in 40 patients (2.2%), and valvular regurgitation or stenosis was found in 488 patients (28%), newly identified in 414 patients (23.8%) [6]. In pilot studies, screening CT coronary angiography has identified clinically significant CAD requiring percutaneous or surgical revascularization in asymptomatic survivors of Hodgkin lymphoma exposed to mediastinal radiation therapy; larger studies are needed to determine the utility of this approach for identifying CAD in cancer survivors at high risk [7][8][9][10].…”
mentioning
confidence: 99%